PENGARUH PELAKSANAAN PROGRAM KESEJAHTERAAN TERHADAP DISIPLIN KERJA KARYAWAN ASKES - Jasman Syaripuddin (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2015)
ABSTRACT This study aims to determine whether the implementation of welfare programs capable of creating an effective employee discipline and know how to influence the implementation of wellness programs to employees of companies in improving employee discipline. the Data collection techniques in this study was a questionnaire (Questionnaire) and documentation study. The Data analysis technique used the produc tmoment correlation, the test and determination. From the analysis result of the research data could be concluded that there is the influence of employee welfare to the discipline of employees at PT Askes branch of Medan. Influence the implementation of welfare programs to the work discipline also showed significant gains. Thus the wellfare was important as factors that affecting the work discipline of employees. Keywords: Welfare Program, Work Discipline.